Crustal heat flow measurements in western Anatolia from borehole equilibrium temperatures - ERKAN, KAMİL (My University, 2014)
Results of a crustal heat flow analysis in western Anatolia based on borehole equilibrium temperatures and rock thermal conductivity data are reported. The dataset comprises 113 borehole sites that were collected in Southern Marmara and Aegean 5 regions of Turkey in 1995–1999. The measurements are from abandoned water wells with depths of 100–150 m. Data were first classed in terms of quality, and the low quality data, including data showing effects of hydrologic disturbances on temperatures, were eliminated. For the remaining 34 sites, one meter resolution temperature-depth curves were carefully analyzed for determination of the background geothermal gra10 dients, and any effects of terrain topography and intra-borehole fluid flow were corrected when necessary. Thermal conductivities were determined either by direct measurements on representative surface outcrop or estimated from the borehole lithologic records. The calculated heat flow values are 85–90 mW m−2 in the northern and central parts of the Menderes horst-graben system. Within the system, the highest heat flow values (> 100 mW m−2 are observed in the northeastern part of Gediz Graben, near Kula active volcanic center. The calculated heat flow values are also in agreement with the results of studies on the maximum depth of seismicity in the region. In the Menderes horst-graben system, surface heat flow is expected to show significant variations as a result of active sedimentation and thermal refraction in grabens, and active erosion on horst detachment zones. High heat flow values (90–100 mW m−2 are also observed in the peninsular (western) part of Çanakkale province. The heat flow anomaly here may be an extension of the high heat flow zone previously observed in the northern Aegean Sea. Moderate heat flow values (60–70 mW m−2 ) are observed in eastern part of Çanakkale and central part of Balıkesir provinces.